Metanephric stromal tumor: A novel pediatric renal neoplasm - Rajalakshmi V; Chandran Philip; Selvambigai; Ganesh Jai (Wolters Kluwer Medknow Publications, 2009)
Metanephric stromal tumor of kidney is a novel pediatric benign stromal specific renal neoplasm. A few cases have been reported in adults also. This tumor is usually centered in the renal medulla with a characteristic microscopic appearance which differentiates this lesion from congenital mesoblastic nephroma and clear cell sarcoma of the kidney. In most cases complete excision alone is curative. The differentiation of metanephric stromal tumor from clear cell sarcoma of the kidney will spare the child from the ill effects of adjuvant chemotherapy. In this communication we describe the gross and microscopic features of metanephric stromal tumor in a one-month-old child with good prognosis.